Application of Kuntowijoyo Prophetic Education to Improve Understanding of Social Studies Learning - Nur Alfiyani; Saliman Saliman (JURNAL PENDIDIKAN IPS, 2024)
Social studies learning methods require methods that can integrate cognitive and spiritual aspects. This research aims to improve the understanding of class VII students at SMP Qur'an Al-Muanawiyah on the material knowing the location of residence in the Social Sciences (IPS) subject through applying the prophetic education approach introduced by Kuntowijoyo. The research method used is Classroom Action Research (PTK) with two cycles, namely cycle I using conventional learning methods and cycle II applying Kuntowijoyo's prophetic education approach. Data was collected through tests, observations, interviews, and documentation. The research results showed a significant increase in students' understanding after implementing the prophetic education approach, with the average student score increasing by 47.63%. In addition, there was an increase in students' active participation in class discussions, especially in spiritual reflection. Students begin to integrate concepts such as caliphate and trust into their reflections, seeing the environment as a spiritual responsibility that must be safeguarded. The majority of students also plan to take real action to preserve the environment. This research proves that Kuntowijoyo's prophetic educational approach to social studies learning can improve students' academic understanding while fostering spiritual awareness that encourages environmental conservation.